2007
DOI: 10.1002/jccs.200700064
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents from the Roots of Patrinia Rupestris

Abstract: Phytochemical investigation of the roots of Patrinia rupestris afforded a new triterpenoid patrirupin A (1) and a new iridoid patrirupin B (2), as well as three known triterpenoids: 3‐oxo‐olean‐12‐en‐28‐oic acid (3), ursolic acid (4), α‐amyrin (5), three known iridoids: isovaltratum (6), 11‐ethoxyviburtinal (7), homobaldrinal (8), five known steroids: ergosterol (9), ergost‐6,22‐diene‐3β,5α,8α‐triol (10), 6‐hydroxenone (11), β‐sitosterol (12), daucosterol (13), and two known flavones: 1‐hydroxy‐5‐methoxy xanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Its molecular formula of ( (Yang, Yuan, & Jia, 2007), which was confirmed by HMBC correlations of 1 ( Figure 1). Detailed NMR analysis of 1 indicated the presence of two ethoxy groups.…”
Section: Resultsmentioning
confidence: 63%
“…Its molecular formula of ( (Yang, Yuan, & Jia, 2007), which was confirmed by HMBC correlations of 1 ( Figure 1). Detailed NMR analysis of 1 indicated the presence of two ethoxy groups.…”
Section: Resultsmentioning
confidence: 63%
“…By analyzing the NMR spectroscopic data of compounds 3-6, and comparing their physical and spectroscopic data with those reported in the literature, the known iridoids were identified as rupesin B (3) [16], homobaldrinal (4) [17], baldrinal (5) [18], and 11-methoxyviburtinal (6) [18].…”
Section: Resultsmentioning
confidence: 96%
“…Compared with peak 55 and a previous study [10], the m/z = 151 indicated an Aring fragment of flavanones combined with a hydroxy group. So peak 36 was finally proposed as 3′,4′,5,7-tetrahydroxyflavanone [29]. Peak 54 and peak 56 (Fig.…”
Section: Resultsmentioning
confidence: 99%